SOLUTIONS TO PROVIDE ENERGY SAVING IN TECHNOLOGICAL MACHINES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This scientific article analyzes modern approaches to ensuring energy efficiency in technological machines. It covers technological, management and design solutions related to reducing energy consumption, increasing production efficiency, rational use of resources and ensuring environmental safety. The possibilities of increasing energy efficiency through frequency control systems, energy-efficient electric motors, heat recovery methods, digitalization and optimization mechanisms based on artificial intelligence are widely disclosed. The impact of the maintenance system and material selection on energy is also analyzed in detail. The ideas put forward in this essay serve to ensure the sustainable development of industrial enterprises and their operation in accordance with international standards.